2012
DOI: 10.1038/ki.2012.74
|View full text |Cite
|
Sign up to set email alerts
|

Moderation of dietary sodium potentiates the renal and cardiovascular protective effects of angiotensin receptor blockers

Abstract: Dietary sodium restriction has been shown to enhance the short-term response of blood pressure and albuminuria to angiotensin receptor blockers (ARBs). Whether this also enhances the long-term renal and cardiovascular protective effects of ARBs is unknown. Here we conducted a post-hoc analysis of the RENAAL and IDNT trials to test this in patients with type 2 diabetic nephropathy randomized to ARB or non-renin-angiotensin-aldosterone system (non-RAASi)-based antihypertensive therapy. Treatment effects on renal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
140
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 220 publications
(149 citation statements)
references
References 35 publications
8
140
1
Order By: Relevance
“…According to the sodium DFQ55 in this study, participants exhibited relatively lower levels of sodium consumption (105.1 mEq at week 0 and 78.6 mEq at week 16, which are equivalent to sodium intakes of 2.4 and 1.8 g/d, respectively) than typically consumed by Korean populations or reported in previous studies (24)(25)(26). These underestimated DFQ55 values may reflect the inexactitude of sodium intake estimation only by dietary recall.…”
Section: Discussionmentioning
confidence: 53%
“…According to the sodium DFQ55 in this study, participants exhibited relatively lower levels of sodium consumption (105.1 mEq at week 0 and 78.6 mEq at week 16, which are equivalent to sodium intakes of 2.4 and 1.8 g/d, respectively) than typically consumed by Korean populations or reported in previous studies (24)(25)(26). These underestimated DFQ55 values may reflect the inexactitude of sodium intake estimation only by dietary recall.…”
Section: Discussionmentioning
confidence: 53%
“…Therapeutic options for patients with persistent albuminuria in the setting of satisfactory HbA 1c and BP control are limited to changes in lifestyle, such as sodium restriction and weight loss, which are supported by limited evidence and are often difficult to achieve [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Extracellular volume restriction, by means of moderating dietary sodium intake or concomitant diuretic treatment has been shown to improve the albuminuria‐reducing and blood pressure‐lowering response to RAAS blockade as well as the efficacy of RAAS blockade to decrease cardio‐renal risk 5, 14, 15. The present study shows that NT‐proBNP can help to identify individuals who may not respond to dual RAAS inhibition with aliskiren and who may benefit from diuretic treatment or dietary sodium‐lowering.…”
Section: Discussionmentioning
confidence: 63%
“…People with type 2 diabetes are susceptible to retaining sodium and fluid as a result of disturbed insulin homeostasis 3. Previous studies have shown that sodium retention and subsequent volume overload are the main determinants of poor response to RAAS therapy 4, 5. Accordingly, volume restriction by means of co‐diuretic treatment or a low sodium diet enhances the blood pressure‐lowering and albuminuria‐reducing effects of RAAS inhibition 6.…”
Section: Introductionmentioning
confidence: 99%